PERAN MEDIASI STRES KERJA PADA PENGARUH JOB INSECURITY DAN BEBANKERJA TERHADAP TURNOVER INTENTION KARYAWAN ( Studi Kasus Pada Karyawan Outsourcing PT. DVN ) - Titi Setyawati; Widhy Setyowati (Magister Manajemen STIE Bank BPD Jateng, 2021)
The purpose of this study was to analyze work stress on work stress. To analyze the effect of workload on work stress. Analyze the effect of job insecurity on turnover intention. Analyze the effect of workload on turnover intention. Analyze the effect of job satisfaction on turnover intention. Techniques regarding datausing a questionnaire by applying a questionnaire to PT.DVN employees. The results are Job insecurity has apositive and significant effect on work stress, workload has a positive and significant effect on work stress,job insecurity has a positive and significant effect on turnover intention, workload has a significant effect on positive and positive work turnover on turnover intention, job insecurity has a significant effect on turnoverintention. positive effect on turnover intention through work stress, and workload has a positive effect on turn over intention through work stress.